TINJAUAN HUKUM TERHADAP PUTUSAN HAKIM DALAM PERKARA TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK - Nopiana Mozin (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
For the sake of realizing a prosperous, just and prosperous Indonesian society based on Pancasila and the 1945 Constitution. The quality of Indonesia's human resources must be continuously improved for national development capital and making Indonesia a developed country. It also includes attention to youth and children as the next generation, so that one day they can bring Indonesia into a developed country. Talking about the problem of adolescents and children is an interesting subject to be discussed and discussed hotly these years of years the level of juvenile delinquency in narcotics abuse, brawl that leads to criminal acts, more specifically criminal acts of theft perpetrated by children. In the current era, we hear a lot of theft, both adults and young children. According to article 1 number 1 of the Child Protection Act, "a child is someone who is not yet 18 years (eighteen) years old, including those still in the womb". In juvenile criminal law, hereinafter referred to as Delinquency / (crime) against several acts that are against the law. According to Romli Atmasasmit Juvenile (15), Delinquency is any act or behavior of a child under the age of 18 years and has not married which is a violation of applicable legal norms, and can endanger the child's personal development.